New potentiometric electrode based on ion pair complex for determination of tropicamide in pure and pharmaceutical formulations - Mouhammed Khateeb; Basheer Elias; Hazar Alksair (Journal of Electrochemical Science and Engineering, 2016)
Construction and general performance of a novel modified carbon paste electrode (MCPE) for determination of tropicamide (TPC) in pure form and pharmaceutical formulations have been examined. Tropicamide-tetraphenylborate (TPC–TPB) ion pair has been prepared and used as electroactive material. The best MCPE electrode was composed of 7 % ion-pair, 46.5 % dioctylphthalat and 46.5 % graphite powder. The electrode shows stable potentiometric response for TPC in the concentration range 0.3–221.0 µM at 25 °C and pH range of 2.0–8.0. The electrode exhibits near Nernstian slope of 59.71±0.30 mV/decade and lower limit of detection of 0.09 µM with fast response time (less than 15 s). The selectivity of the electrode (TPC–TPB) was investigated with respect to some organic and inorganic cations. The MCPE was designed to have better mechanical resistance. The proposed method was successfully applied for determination of TPC in eye drop formulation.